Improved T-shaped quartz tuning fork with isosceles-trapezoidal grooves optimized for quartz-enhanced photoacoustic spectroscopy - Feihu Fang; Runqiu Wang; Dongfang Shao; Yi Wang; Yilü Tao; Shengshou Lin; Yufei Ma; Jinxing Liang (Photoacoustics)
The quartz tuning fork (QTF) being the acoustic-electrical conversion element for quartz-enhanced photoacoustic spectroscopy (QEPAS) system directly affects the detection sensitivity. However, the low electromechanical conversion efficiency characteristic of standard QTF limits the further enhancement of the system. Therefore, the optimized design for QTF is becoming an important approach to improve the performance of QEPAS. In this work, 9 kHz T-shaped QTFs with isosceles-trapezoidal grooves are firstly applied to gas sensing experiments. Four types of 9 kHz QTFs are fabricated and applied to gas detection experiments. Simulation results reveal QTFs with isosceles-trapezoidal grooves are conducive to optimizing the stress distribution and enhancing electromechanical conversion efficiency. The results of the gas sensing experiment (acetylene C2H2) indicate that the signal peak and signal-to-noise ratio values of T-shaped QTF with positive isosceles-trapezoidal grooves can reach 1.44 and 1.85 times greater than the normal QTF with rectangular cross-section prongs.